Survey of stress and coping strategies to predict the general health of nursing staff - Javadi-Pashaki, Nazila; Darvishpour, Azar (Journal of Education and Health Promotion, 2019)
BACKGROUND: Nurses are often faced with the variety of work-related stress which could affect their physical and mental health. Coping strategies play an important role in reducing stress and consequently increasing the health and well-being. This study was conducted to investigate the role of stress and coping strategies to predict the general health of nursing staff. SUBJECTS AND METHODS: An analytical cross-sectional design was carried out on 318 nurses working in governmental health centers of Guilan University of Medical Sciences, the North of Iran, in 2017. Data were collected through multistage cluster sampling using self-report questionnaires and demographic characteristics. The study instruments included Hospital Job Stress, Coping Strategies, and General Health Questionnaires. For analysis of data, descriptive statistics and regression test were applied using SPSS software version 19. RESULTS: The results revealed that the highest mean score (47.71 ± 7.88) of different dimensions of coping strategies was related to task-oriented strategy. Furthermore, the results indicated that stress and coping strategies together could explain around 2.5% of variance of general health (ΔR2 = 0.025). However, based on the statistically significant level, the results revealed the coping strategies as the predictor of general health (P = 0.002, beta = 0.094). CONCLUSIONS: The results highlight the importance of considering coping strategies for predicting general health in nurses. Regarding the inevitability of some stressors in the nursing profession and the need to prevent stressful effects, workshops as an effective training method to reduce staff stress should be on the agenda of managers.